Head‐to‐Tail Dimerization of 4‐Fluoroacetophenone in the KOH/DMSO Superbase Suspension and Related SNAr Reaction. Issue 23 (26th May 2020) - Bidusenko, Ivan A.; Schmidt, Elena Yu.; Ushakov, Igor' A.; Orel, Vladimir B.; Absalyamov, Damir Z.; Vitkovskaya, Nadezhda M.; Trofimov, Boris A.
Abstract : The head‐to‐tail autocondensation of 4‐fluoroacetophenone in the KOH/DMSO superbase suspension stops on dimerization step affording 4‐acetylbenzyl‐4'‐fluorophenylketone in 96 % yield. Further condensation of the diketone formed is prevented by a weaker electron‐withdrawing effect of enolate spacer, –CH=C(OK)–. 2‐Fluoro‐ and 3‐fluoroacetophenones are inactive in this reaction. Other superbases of the type MOR/DMSO (M = Na, K; R = H, OBu t ) are inferior in promotion of this reaction providing 71–76 % yields of the dimeric ketone. Other weak acids like non‐fluorinated acylbenzenes prove to be also capable of forming Csp 2 –Csp 3 bond with 4‐fluoroacetophenone under similar conditions. This new group of fluorine substitution (SN Ar) reaction opens a short and simple route to so far inaccessible aromatic diketones via the nucleophilic substitution of fluorine atom in 4‐fluoroacetophenone by available acylbenzenes. The quantum‐chemical rationale of the observed substitution process as competing with aldol condensation is suggested. Abstract : The head‐to‐tail autocondensation of 4‐fluoroacetophenone in the KOH/DMSO superbase suspension stops on dimerization step affording 4‐acetylbenzyl‐4'‐fluorophenylketone. This new fluorine substitution (SN Ar) reaction opens short and simple route to so far inaccessible aromatic diketones via the nucleophilic substitution of fluorine atom in 4‐fluoroacetophenone by available acylbenzenes.